2020
DOI: 10.1007/s00586-020-06554-w
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity and responsiveness of the Dutch version of the AOSpine PROST (Patient Reported Outcome Spine Trauma)

Abstract: Purpose To validate the Dutch version of AOSpine PROST (Patient Reported Outcome Spine Trauma). Methods Patients were recruited from two level-1 trauma centers from the Netherlands. Next to the AOSpine PROST, patients also filled out SF-36 for concurrent validity. Descriptive statistics were used to analyze the characteristics. Content validity was assessed by evaluating the number of inapplicable or missing questions. Also floor and ceiling effects were analyzed. Internal consistency was assessed by calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Also moderate to excellent test-retest reliability was obtained for all individual items. This is in agreement with findings from Sadiqi et al 8,9 in the previous psychometric studies for the AO Spine PROST with a follow-up up to 12 months.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Also moderate to excellent test-retest reliability was obtained for all individual items. This is in agreement with findings from Sadiqi et al 8,9 in the previous psychometric studies for the AO Spine PROST with a follow-up up to 12 months.…”
Section: Discussionsupporting
confidence: 93%
“…Also using the EQ-5D-5L is more informative, since the validity of the AO Spine PROST was already tested in correlation to the SF-36 in previous validation studies. 8,9 In the current study good concurrent validity for the AO Spine PROST was found in comparison to the EQ-5D-5L (r = 0.76; P < 0.001), while slightly lower Copyright r 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations